AB0005 Association of FCGR2A with response to infliximab in rheumatoid arthritis patients. (23rd January 2014) - Montes-Martinez, A.; Perez-Pampin, E.; Narvaez, J.; Cañete, J.D.; Navarro-Sarabia, F.; Moreiras, V.; Fernandez-Nebro, A.; Ordoñez, M.D.C.; Rodriguez de la Serna, A.; Magallanes, B.; Gomez-Reino, J.J.; Gonzalez, A.
Abstract : Background: Receptors for the Fc fragment of IgG play an important role in homeostasis and function of antibodies. In addition of their functions related with endogenous antibodies, they also bind biologic drugs that include the Fc fragment of IgG. Therefore, functional polymorphisms in the FCGR2A, FCGR2B and FCGR3A genes have been considered candidates to affect the response to these drugs. Objectives: We aimed to determine the role of functional Fcγr polymorphisms in the response of patients with RA treated with anti-TNF Methods: The study has included 299 Spanish patients with RA treated with anti-TNF (52.5% infliximab, 30.4% etanercept and 17.1% adalimumab). Disease activity was evaluated basally, and at 3, 6 and 12 months of treatment. Genotypes for H131R ( rs1801274 ) in FCGR2A, F158V ( rs396991 ) in FCGR3A and I231T ( rs1050501 ) in FCGR2B were determined by single base extension. Analyses included linear regression with change in DAS28 (ΔDAS28) and logistic regression comparing responders and non-responders according to the EULAR criteria. An additive genetic model was considered. Covariates included in the analyses were basal DAS28, gender and drug. Results: Genotype call rate was 97.8% and genotypes were in accordance with HWE. Genotype frequencies were similar to the described in studies with Europeans. In the global analysis of the three drugs, there was a trend to a better response in the homozygous HH patients for the FCGR2A SNP (ΔDAS28 linear regression P=0.07 at 3 months; P=0.08 at 12 months). When the EULAR-defined responders were compared with the non-responders the difference was significant at 12 months (P=0.036). Considering separately the three anti-TNF drugs, association of FCGR2A was significant with response to infliximab, both in the analysis of ΔDAS28 (P=0.034 at 3 months and P=0.0076 at 12 months) and in the logistic regression of responders vs non-responders (P=0.036 at 12 months). There was no association between response to treatment and genotypes of FCGR3A or FCGR2B . Conclusions: Our results have shown association of the R allele of FCGR2A with a poor response to anti-TNF, which was more marked in patients treated with infliximab. This SNP should be integrated with other biomarkers to develop therapeutic decision making tools. Disclosure of Interest: None Declared